A kinetic model considering the heterogeneous nature of the enzyme hydrolysis of lignocellulosic materials. (11th April 2019) - Caro, Ildefonso; Blandino, Ana; Díaz, Ana B.; Marzo, Cristina
Abstract: In this work, a mathematical model is proposed to predict the kinetic behaviour of the enzymatic conversion of various types of lignocellulosic biomass into fermentable sugars. Digestion of the cellulosic polymers is carried out using enzymatic hydrolysis under different conditions. Unlike other kinetic models, published previously for this process, this one considers the heterogeneous nature of the process by which a solid, in the form of small particles, is decomposed to monosaccharides by the action of a diverse set of enzymes in solution. The effect of the particle size on the hydrolysis rate has also been taken into consideration. To assess the model's goodness of fit to any general situation, the experimental data obtained in the hydrolysis of three different lignocellulosic residues have been analysed. Thus, the hydrolysis data of wheat straw, rice husks and exhausted sugar beet pellets have been compared with the theoretical values calculated by the model. The results obtained show that this model predicts the enzyme's hydrolysis of lignocellulosic substrates under different conditions very accurately and it could therefore be used efficiently in the optimization of the hydrolysis processes implemented in the bio‐refinery industry. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd